8-Oxoguanine targeted by 8-oxoguanine DNA glycosylase 1 (OGG1) is central to fibrogenic gene activation upon lung injury. Issue 3 (18th January 2023) - Pan, Lang; Hao, Wenjing; Xue, Yaoyao; Wang, Ke; Zheng, Xu; Luo, Jixian; Ba, Xueqing; Xiang, Yang; Qin, Xiaoqun; Bergwik, Jesper; Tanner, Lloyd; Egesten, Arne; et al.
Abstract: Reactive oxygen species (ROS) are implicated in epithelial cell-state transition and deposition of extracellular matrix upon airway injury. Of the many cellular targets of ROS, oxidative DNA modification is a major driving signal. However, the role of oxidative DNA damage in modulation profibrotic processes has not been fully delineated. Herein, we report that oxidative DNA base lesions, 8-oxoG, complexed with 8-oxoguanine DNA glycosylase 1 (OGG1) functions as a pioneer factor, contributing to transcriptional reprogramming within airway epithelial cells. We show that TGFβ1-induced ROS increased 8-oxoG levels in open chromatin, dynamically reconfigure the chromatin state. OGG1 complexed with 8-oxoG recruits transcription factors, including phosphorylated SMAD3, to pro-fibrotic gene promoters thereby facilitating gene activation. Moreover, 8-oxoG levels are elevated in lungs of mice subjected to TGFβ1-induced injury. Pharmacologic targeting of OGG1 with the selective small molecule inhibitor of 8-oxoG binding, TH5487, abrogates fibrotic gene expression and remodeling in this model. Collectively, our study implicates that 8-oxoG substrate-specific binding by OGG1 is a central modulator of transcriptional regulation in response to tissue repair.